Evaluation of Traffic Distribution Performance of ECMP and PCC+CAKE for Multi-ISP Load Balancing on Real Networks Based Using Mikrotik - Fathurrohim, Moh; Basuki, Achmad (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2025)
Imbalance in bandwidth utilization among Internet Service Providers (ISPs) is a major challenge in network management within educational institutions, especially when differences in ISP capacity cause overload on one main path. To address this issue, this study proposes the application of load balancing methods using Equal-Cost Multi-Path (ECMP) and Per-Connection Classifier (PCC) optimized with the CAKE queue type. The implementation is carried out using MikroTik devices, which support the flexible configuration of both methods. Testing is conducted on a real network using a combination of passive monitoring approach—through the analysis of actual traffic and ISP utilization—and active monitoring. The evaluation results show that the ECMP method still produces an uneven traffic distribution, with a tendency to concentrate the load on one path. In contrast, PCC+CAKE is able to distribute traffic more evenly according to the ISP bandwidth ratio. In addition, PCC+CAKE shows more stable performance on throughput, RTT, and jitter, and has very low packet loss. Therefore, PCC+CAKE is recommended as a more effective load balancing method to increase the efficiency of ISP utilization and overall network quality in a multi-ISP environment.